Investments in the development of human capital in the conditions of war: Experience in the context of improving the public administration system - Shpektorenko, Igor; Hrushetskyi, Bohdan; Tryshnovskyi, Ievgen; Dobrianska, Nataliia; Zarichniak, Andrii; Dubytskyi, Denys (Edelweiss Applied Science and Technology, 2024)
The article represents socio-political, economic, and historical research of the landscape of war conflicts’ consequences for human capital development. Both evident, statistically described and well-researched and latent, not evident and not ‘surface’ consequences are analyzed. Cases of Syria, Iraq, and Ukraine are considered based on dialectics and systemic-structural approach, in the plane of dynamics of human capital and efforts of these states in maintenance and development of human capital during war conflicts.